1999
DOI: 10.1016/s1074-7613(00)80038-2
|View full text |Cite
|
Sign up to set email alerts
|

Impaired On/Off Regulation of TNF Biosynthesis in Mice Lacking TNF AU-Rich Elements

Abstract: We addressed the impact of deleting TNF AU-rich elements (ARE) from the mouse genome on the regulation of TNF biosynthesis and the physiology of the host. Absence of the ARE affected mechanisms responsible for TNF mRNA destabilization and translational repression in hemopoietic and stromal cells. In stimulated conditions, TNF ARE were required both for the alleviation and reinforcement of message destabilization and translational silencing. Moreover, the mutant mRNA was no longer responsive to translational mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

55
1,209
2
34

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 1,266 publications
(1,300 citation statements)
references
References 51 publications
55
1,209
2
34
Order By: Relevance
“…Earlier studies with TNF-deficient animals demonstrated the critical role of TNF in mediating anti-bacterial host defenses and supporting development of secondary lymphoid organ structure and function [31,42]. In further studies, Tg overexpression of TNF revealed its crucial involvement in the pathogenesis of arthritis [52] and Crohn's-like inflammatory bowel disease [53]. With reference to autoimmune disease pathogenesis, in various animal models of autoimmunity, the role of TNF is shown to be both proinflammatory and immuneor disease-suppressive [34].…”
Section: Discussionmentioning
confidence: 98%
“…Earlier studies with TNF-deficient animals demonstrated the critical role of TNF in mediating anti-bacterial host defenses and supporting development of secondary lymphoid organ structure and function [31,42]. In further studies, Tg overexpression of TNF revealed its crucial involvement in the pathogenesis of arthritis [52] and Crohn's-like inflammatory bowel disease [53]. With reference to autoimmune disease pathogenesis, in various animal models of autoimmunity, the role of TNF is shown to be both proinflammatory and immuneor disease-suppressive [34].…”
Section: Discussionmentioning
confidence: 98%
“…The JNK group is activated by exposure of cells to cytokines and to environmental stress (for review, Whitmarsh & Davis, 1996). JNK isoforms, encoded by three genes, phosphorylate-specific sites (serines 63 and 73) on the amino-transactivation domain of cjun following exposure to ultra-violet (UV) irradiation, growth factors or cytokines (Devary et al, 1992;Kallunki et al, 1994;Kontoyiannis et al, 1999). JNK-1 and JNK-2 have been identified in the lungs of mammals, while JNK-3 has been located to the brain .…”
Section: Introductionmentioning
confidence: 99%
“…TNF mRNA stability is mediated by cis-acting adenosine/uridine-rich elements (ARE) within the 3'UTR. Deletion of ARE from the mouse genomic TNF locus results in elevated basal and LPS-induced TNF expression, chronic inflammatory arthritis and inflammatory Bowel disease [24]. COX-2 mRNA contains 3'UTR similar to those of TNF and is post-transcriptionally modulated in a similar way [17].…”
Section: Discussionmentioning
confidence: 99%